Implementasi Environmental Education Day: Water, Climate, and Sustainability di SDN Sardonoharjo 1 melalui Hands-On dan Game-Based Learning untuk Membangun Literasi Iklim Berkelanjutan - Prawitasari, Diah Ayu; Nuurussyahba, Wahda Annisa; Mustofa, Ikrom (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
The Environmental Education Day: Water, Climate, and Sustainability activity at SDN Sardonoharjo 1 was implemented to foster sustainable climate literacy among elementary school students through an interactive and contextual learning approach. This activity employed a descriptive qualitative method with a single case study design, involving fourth, fifth, and sixth-grade students in a series of hands-on and game-based learning activities tailored to their developmental levels. The results show that this learning model significantly improved students’ understanding of water and climate concepts through concrete and enjoyable learning experiences. Students demonstrated enhanced ability to relate the hydrological cycle and climate change concepts to real-world phenomena and logically identify the causes and impacts of climate change. Furthermore, the activity strengthened 21st-century skills such as critical thinking, communication, collaboration, and creativity, as evidenced by active participation, problem-solving ability, and the quality of student-produced posters. Other findings indicate an increase in ecological awareness and environmentally friendly behavior, reflected in students’ reflective attitudes during games and classroom discussions. This program proved effective in instilling sustainability values from an early age and can serve as a replicable learning model for strengthening environmental education at the elementary school level.